Analysis of The Influence of Islamic Branding, Halal Awarness and Product Quality on The Purchase Decision of Soka Brand Halal Socks - Sera Nabila Alitakrim; Hilda Monoarfa; Firmansyah Firmansyah (Review of Islamic Economics and Finance, 2021)
AbstractPurpose - The purpose of this study is to analyze whether there is an influence of Islamic branding factors, halal awareness and product quality on purchasing decisions of soka brand halal socks in Indonesia.Methodology - The research method used is descriptive quantitative with technical data analysis using the SEM-PLS method. The research data were obtained from consumers of halal criteria socks in Indonesia, perhaps 210 people.Findings - The results showed that the level of Islamic brands, halal awareness and product quality were in the high category. The Islamic branding variable has no effect on the decision to purchase halal socks, besides that the variable of halal awareness and product quality has a positive influence on the purchase decision of halal soka brand socks. This research is expected to be able to provide benefits for various parties in increasing public understanding of halal fashion, especially halal socks, in order to increase awareness of the halal fashion industry in IndonesiaKeywords: Islamic branding, halal awareness, product quality, halal socks